Preparation process of high-wear-resistance magnesia carbon brick

By adding diamond, corundum, silicon carbide and other materials to the magnesium carbon brick preparation process and strictly inspecting and processing the wear resistance, the problem of insufficient wear resistance of magnesium carbon bricks is solved, and its wear resistance and stability in harsh environments is significantly improved.

CN119859054APending Publication Date: 2025-04-22JIANGSU SUJIA GROUP NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411718362.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing magnesium carbon brick preparation process has a general wear resistance after forming, and cannot withstand large impacts and frictions in high temperature and high corrosive environments. The detection process is not thorough enough to ensure the stable wear resistance of magnesium carbon bricks.

Method used

The high wear resistance magnesium carbon brick preparation process is adopted. By proportional ratios of magnesium sand particles, magnesium sand powder, graphite, phenolic resin, antioxidants, diamond, corundum, silicon carbide, and injecting into the mold through an injection machine. After sintering and forming, samples are taken in batches for wear resistance testing, and magnesium carbon bricks are processed based on the detection results.

Benefits of technology

The wear resistance of magnesium carbon bricks is significantly improved, so that it can withstand large impacts and frictions in high temperature and high corrosion environments, ensuring the safety and stability of magnesium carbon bricks. At the same time, through a thorough inspection process, the wear resistance of magnesium carbon bricks meets the stable standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-wear-resistance magnesia carbon brick, which comprises the following steps: (1) mixing raw materials: proportioning magnesia particles, magnesia powder, graphite, phenolic resin, an antioxidant, diamond, corundum and silicon carbide in proportion, and mixing the proportioned materials to obtain the raw materials; (2) sintering and molding: injecting the mixed raw materials into a magnesia carbon brick mold by adopting an injection machine, preparing materials, pushing the mold into a kiln, and sintering and molding; and (3) sampling treatment: extracting a sample from the formed magnesia carbon brick according to the proportion, and detecting. According to the preparation process of the high-wear-resistance magnesia carbon brick, diamond, corundum and silicon carbide are adopted, so that the wear resistance of the magnesia carbon brick is further enhanced, the magnesia carbon brick can bear large impact and friction in a high-temperature and high-corrosion environment, and the safety and stability of the magnesia carbon brick in use are higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesia carbon brick preparation, in particular to a process for preparing magnesia carbon bricks with high wear resistance. Background Art

[0002] Magnesia carbon bricks are non-burning carbon composite refractory materials made of high melting point basic oxide magnesium oxide (melting point 2800℃) and high melting point carbon material that is difficult to be wetted by slag as raw materials, adding various non-oxide additives and combining them with carbonaceous binders.

[0003] The preparation process of magnesia carbon bricks on the market, when preparing magnesia carbon bricks, mostly uses simple components such as magnesium powder, magnesium particles, graphite, etc., which leads to the problem of general wear resistance after molding. The use environment of magnesia carbon bricks is relatively harsh, with high ambient temperature and corrosion, large impacts in the environment, and high wear. When magnesia carbon bricks are placed in this environment, they are prone to damage, which is not conducive to the subsequent safe and stable use of magnesia carbon bricks. At the same time, the detection process in the preparation process is not thorough enough, and it is impossible to thoroughly test the wear resistance of magnesia carbon bricks to ensure that the magnesia carbon bricks have stable wear resistance after manufacturing. For this reason, we propose a preparation process for magnesia carbon bricks with high wear resistance. Summary of the invention

[0004] The object of the present invention is to provide a process for preparing magnesia carbon bricks with high wear resistance to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a process for preparing a highly wear-resistant magnesia-carbon brick, wherein the steps of the process for preparing a highly wear-resistant magnesia-carbon brick are as follows:

[0006] (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials;

[0007] (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering;

[0008] (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing;

[0009] (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness;

[0010] (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample;

[0011] Preferably, the raw materials are prepared by proportioning: 15-30 parts of magnesia particles, 10-15 parts of magnesia powder, 12-18 parts of graphite, 5-8 parts of phenolic resin, 3-8 parts of antioxidant, 10-15 parts of diamond, 3-6 parts of corundum and 5-8 parts of silicon carbide, and then mixing the proportioned materials in a mixer to obtain the raw materials.

[0012] Preferably, the sintering molding is as follows: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 200-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 400-600°C for sintering molding.

[0013] Preferably, the sintering molding is as follows: pushing the mold into a kiln, sintering at 1650-2000° C. for 2-3 hours to obtain a molded magnesia carbon brick.

[0014] Preferably, the sampling process is as follows: randomly taking samples of 1-3 portions out of every 100 portions of the formed magnesia carbon bricks for subsequent testing.

[0015] Preferably, the molding identification is as follows: for the molded magnesia carbon brick sample, a micrometer is used to detect the size, and a roughness tester is used to detect the surface roughness of the magnesia carbon brick.

[0016] Preferably, the samples are compared during the forming identification, and the sample sizes and surface roughness are compared. When the size error exceeds 1-3mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 20-40 samples are taken from the same batch of samples for every 100 samples, and then the forming identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for forming identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

[0017] Preferably, the finished product testing: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 300-500 times, to test the friction resistance of the end wall of the magnesia carbon brick sample.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The preparation process of the highly wear-resistant magnesia carbon bricks is not thoroughly tested. It is just a simple test of the corrosion resistance and hardness of the magnesia carbon bricks. In this process, the magnesia carbon bricks are sampled in batches, and the samples are tested for wear resistance. If the error is large, more samples are taken from the batch again for testing, and the magnesia carbon bricks are processed according to the test results to ensure the wear resistance of the magnesia carbon bricks.

[0020] 2. The preparation process of this highly wear-resistant magnesia carbon brick uses diamond, corundum and silicon carbide to further enhance the wear resistance of magnesia carbon bricks, so that magnesia carbon bricks can withstand greater impact and friction in high temperature and highly corrosive environments, making magnesia carbon bricks safer and more stable when used. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] The present invention provides a technical solution: a process for preparing a magnesia-carbon brick with high wear resistance, wherein the steps of the process for preparing a magnesia-carbon brick with high wear resistance are as follows:

[0023] (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials;

[0024] (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering;

[0025] (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing;

[0026] (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness;

[0027] (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample;

[0028] Preferably, the raw materials are prepared by proportioning: 15-30 parts of magnesia particles, 10-15 parts of magnesia powder, 12-18 parts of graphite, 5-8 parts of phenolic resin, 3-8 parts of antioxidant, 10-15 parts of diamond, 3-6 parts of corundum and 5-8 parts of silicon carbide, and then mixing the proportioned materials in a mixer to obtain the raw materials.

[0029] Preferably, the sintering molding is as follows: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 200-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 400-600°C for sintering molding.

[0030] Preferably, the sintering molding is as follows: pushing the mold into a kiln, sintering at 1650-2000° C. for 2-3 hours to obtain a molded magnesia carbon brick.

[0031] Preferably, the sampling process is as follows: randomly taking samples of 1-3 portions out of every 100 portions of the formed magnesia carbon bricks for subsequent testing.

[0032] Preferably, the molding identification is as follows: for the molded magnesia carbon brick sample, a micrometer is used to detect the size, and a roughness tester is used to detect the surface roughness of the magnesia carbon brick.

[0033] Preferably, the samples are compared during the forming identification, and the sample sizes and surface roughness are compared. When the size error exceeds 1-3mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 20-40 samples are taken from the same batch of samples for every 100 samples, and then the forming identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for forming identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

[0034] Preferably, the finished product testing: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 300-500 times, to test the friction resistance of the end wall of the magnesium carbon brick sample;

[0035] Example 2:

[0036] A process for preparing a highly wear-resistant magnesia-carbon brick, the steps of which are as follows:

[0037] (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials;

[0038] (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering;

[0039] (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing;

[0040] (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness;

[0041] (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample;

[0042] Preferably, the raw materials are prepared by proportioning: 20-30 parts of magnesia particles, 12-15 parts of magnesia powder, 13-18 parts of graphite, 5-7 parts of phenolic resin, 4-7 parts of antioxidant, 12-15 parts of diamond, 4-6 parts of corundum and 5-7 parts of silicon carbide, and then mixing the proportioned materials in a mixer to obtain the raw materials.

[0043] Preferably, the sintering molding is as follows: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 280-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 450-600°C for sintering molding.

[0044] Preferably, the sintering molding is as follows: the mold is pushed into a kiln, sintered at 1750-2000° C. for 2-3 hours to obtain a molded magnesia carbon brick.

[0045] Preferably, the sampling process is as follows: randomly taking samples of 1-3 portions out of every 100 portions of the formed magnesia carbon bricks for subsequent testing.

[0046] Preferably, the molding identification is as follows: for the molded magnesia carbon brick sample, a micrometer is used to detect the size, and a roughness tester is used to detect the surface roughness of the magnesia carbon brick.

[0047] Preferably, the samples are compared during the forming identification, and the sample sizes and surface roughness are compared. When the size error exceeds 2-3mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 30-40 samples are taken from the same batch of samples for every 100 samples, and then the forming identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for forming identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

[0048] Preferably, the finished product testing: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 400-500 times, to test the friction resistance of the end wall of the magnesia carbon brick sample;

[0049] Example 3:

[0050] A process for preparing a highly wear-resistant magnesia-carbon brick, the steps of which are as follows:

[0051] (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials;

[0052] (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering;

[0053] (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing;

[0054] (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness;

[0055] (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample;

[0056] Preferably, the raw materials are prepared by proportioning: 25-30 parts of magnesia particles, 13-15 parts of magnesia powder, 14-18 parts of graphite, 5-6 parts of phenolic resin, 4-6 parts of antioxidant, 13-15 parts of diamond, 5-6 parts of corundum and 6-7 parts of silicon carbide, and then mixing the proportioned materials in a mixer to obtain the raw materials.

[0057] Preferably, the sintering molding is as follows: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 280-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 450-500°C for sintering molding.

[0058] Preferably, the sintering molding is as follows: the mold is pushed into a kiln, sintered at 1850-2000° C. for 2-3 hours to obtain a molded magnesia carbon brick.

[0059] Preferably, the sampling process is as follows: randomly taking samples of 1-3 portions out of every 100 portions of the formed magnesia carbon bricks for subsequent testing.

[0060] Preferably, the molding identification is as follows: for the molded magnesia carbon brick sample, a micrometer is used to detect the size, and a roughness tester is used to detect the surface roughness of the magnesia carbon brick.

[0061] Preferably, the samples for molding identification are compared, and the sample sizes and surface roughness are compared. When the size error exceeds 2-3mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 35-40 samples are taken from the same batch of samples for every 100 samples, and then molding identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for molding identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

[0062] Preferably, the finished product testing: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 450-500 times, to test the friction resistance of the end wall of the magnesia carbon brick sample;

[0063] Example 4:

[0064] A process for preparing a highly wear-resistant magnesia-carbon brick, the steps of which are as follows:

[0065] (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials;

[0066] (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering;

[0067] (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing;

[0068] (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness;

[0069] (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample;

[0070] Preferably, the raw materials are prepared by proportioning: 28 parts of magnesia particles, 14 parts of magnesia powder, 15 parts of graphite, 5 parts of phenolic resin, 6 parts of antioxidant, 15 parts of diamond, 6 parts of corundum and 7 parts of silicon carbide, and then mixing the proportioned materials with a mixer to obtain the raw materials.

[0071] Preferably, the sintering molding is as follows: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 280-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 490°C for sintering molding.

[0072] Preferably, the sintering molding is as follows: the mold is pushed into a kiln, sintered at 1900° C. for 3 hours to obtain a molded magnesia carbon brick.

[0073] Preferably, the sampling process is as follows: randomly taking samples of 1-3 portions out of every 100 portions of the formed magnesia carbon bricks for subsequent testing.

[0074] Preferably, the molding identification is as follows: for the molded magnesia carbon brick sample, a micrometer is used to detect the size, and a roughness tester is used to detect the surface roughness of the magnesia carbon brick.

[0075] Preferably, the samples for molding identification are compared, and the sample sizes and surface roughness are compared. When the size error exceeds 2mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 38 samples are taken from the same batch of samples for every 100 samples, and then molding identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for molding identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

[0076] Preferably, the finished product testing: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 500 times, to test the friction resistance of the end wall of the magnesia carbon brick sample.

[0077] Working principle: For this type of high wear-resistant magnesia carbon brick preparation process, the inspection is not thorough enough, and it is just a simple corrosion resistance and hardness test for the magnesia carbon brick. In this process, the magnesia carbon bricks are sampled in batches, and the samples are tested for wear resistance. If the error is large, more samples are taken from the batch for testing again, and the magnesia carbon bricks are processed based on the test results to ensure the wear resistance of the magnesia carbon bricks. In addition, this process uses diamond, corundum, and silicon carbide to further enhance the wear resistance of the magnesia carbon bricks, so that the magnesia carbon bricks can withstand greater impact and friction in high temperature and highly corrosive environments, making the magnesia carbon bricks safer and more stable when used, thus completing the entire use process of the high wear-resistant magnesia carbon brick preparation process.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the appended claims and their equivalents.

Claims

1. A process for preparing highly wear-resistant magnesia-carbon bricks, characterized in that: The steps of the preparation process of the highly wear-resistant magnesia carbon brick are as follows: (1) Mixing raw materials: mixing magnesia particles, magnesia powder, graphite, phenolic resin, antioxidant, diamond, corundum, and silicon carbide in proportion, and then mixing the proportioned materials to obtain raw materials; (2) Sintering: The mixed raw materials are injected into the magnesia carbon brick mold by an injection machine to prepare the materials, and then the mold is pushed into the kiln for sintering; (3) Sampling and processing: extract samples from the formed magnesia carbon bricks according to proportion and conduct testing and processing; (4) Forming identification: After forming, the magnesia carbon brick samples are tested for size and surface smoothness; (5) Finished product testing: Use a wear resistance tester to grind the end wall of the magnesia carbon brick sample to test the corrosion resistance of the magnesia carbon brick sample; 2. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The raw material ratio is as follows: 15-30 parts of magnesia particles, 10-15 parts of magnesia powder, 12-18 parts of graphite, 5-8 parts of phenolic resin, 3-8 parts of antioxidant, 10-15 parts of diamond, 3-6 parts of corundum and 5-8 parts of silicon carbide are mixed in proportion, and the mixed materials are mixed in a mixer to obtain the raw material.

3. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The sintering molding: the mixed raw materials are injected into a magnesia carbon brick mold preheated to 200-350°C by an injection machine to prepare the materials, and then the mold is pushed into a kiln preheated to 400-600°C for sintering molding.

4. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The sintering molding: pushing the mold into a kiln, adopting 1650-2000° C., sintering for 2-3 hours to obtain a formed magnesia carbon brick.

5. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The sampling process is as follows: randomly taking 1 to 3 samples out of every 100 pieces of formed magnesia carbon bricks for subsequent testing.

6. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The molding identification: the size of the formed magnesia carbon brick sample is detected by a micrometer caliper, and the surface roughness of the magnesia carbon brick is detected by a roughness tester.

7. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 6, characterized in that: The samples for molding identification are compared, and the sample size and surface roughness are compared. When the size error exceeds 1-3mm in length, width and height, and the surface roughness error exceeds 0.1-0.2μm, 20-40 samples are taken from the same batch of samples for every 100 samples, and then molding identification is carried out. If it exceeds the standard again, the batch of magnesia carbon bricks will be treated as defective products. If it does not exceed the standard, 1-3 samples are taken from the batch of magnesia carbon brick products for every 100 samples for molding identification. If the identification structure does not exceed the standard, the batch of samples will be treated according to the qualified standards.

8. The process for preparing a highly wear-resistant magnesia-carbon brick according to claim 1, characterized in that: The finished product inspection: using a wear resistance tester, according to the friction pressure of 20±0.2N, the friction speed of 43cpm, the friction number of 300-500 times, to detect the friction resistance of the end wall of the magnesia carbon brick sample.